2004
DOI: 10.1111/j.1600-0501.2004.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the biocompatibility of contaminated implant surfaces treated with an Er : YAG laser and an air powder system

Abstract: Titanium platelets with a sand-blasted and acid-etched surface were coated with bovine serum albumin and incubated with a suspension of Porphyromonas gingivalis (ATCC 33277). Four groups with a total of 48 specimens were formed. Laser irradiation of the specimens (n = 12) was performed on a computer-controlled XY translation stage at pulse energy 60 mJ and frequency 10 pps. Twelve specimens were treated with an air powder system. After the respective treatment, human gingival fibroblasts were incubated on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(125 citation statements)
references
References 48 publications
6
115
0
3
Order By: Relevance
“…15 Moreover, some of these treatment modalities led to undesirable outcomes such as implant surface alteration, bacterial resistance. 16,17 So, novel approaches are still necessary to solve this problem. Photodynamic therapy (PDT) is a simple, non-invasive technique that proved to have anti-bacterial effects according to the findings of previous authors.…”
Section: Introductionmentioning
confidence: 99%
“…15 Moreover, some of these treatment modalities led to undesirable outcomes such as implant surface alteration, bacterial resistance. 16,17 So, novel approaches are still necessary to solve this problem. Photodynamic therapy (PDT) is a simple, non-invasive technique that proved to have anti-bacterial effects according to the findings of previous authors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that treatment of P.gingivalis-contaminated sand-blasted and acid-etched titanium implant surfaces using Er:YAG laser irradiation is capable of allowing attachment of osteoblast cells (8). In another study, it was reported that Er:YAG laser irradiation treatment of P.gingivalis-contaminated rough titanium surfaces resulted in greater fibroblast proliferation on the implant surfaces when compared with sterile specimens (63). In addition, no temperature elevations at the implant-bone interface during implant surface decontamination with the use of the Er:YAG laser in vivo were reported (64).…”
Section: Implant Therapymentioning
confidence: 95%
“…Romanos et al [75] established that cell attachment and morphology after laser irradiation is equal to that of sterile implant surfaces. Kreisler et al [47] examined the biocompatibility of contaminated implant surfaces after treatment with either a particle beam device or the Er:YAG laser. The lowest cell growth and proliferation was seen for contaminated Ti surfaces, while cell growth was significantly greater on sterile (new), air powdertreated, and Er:YAG laser-cleaned surfaces.…”
Section: Laser-based Methodsmentioning
confidence: 99%
“…Several manufacturers have fabricated tip designed to apply the particle beam into subgingival implant surfaces; however, the pattern of the threads causes many regions on the surface to be protected. It must be recognized that air-powder abrasion causes undesirable microscopic alterations of titanium implant surfaces, and so are not ideal [47].…”
Section: Methods Which Have Attempted To Clean Implant Surfacesmentioning
confidence: 99%